La Monjita Rabadilla Blanca (Xolmis velatus), una nueva especie para la Argentina - Wioneczak, Marcelo Javier; Seko Pradier, Luis; Krause, Luis Orlando; Pavese, Nicolás (Nuestras Aves, 2018)
Este artículo no cuenta con un resumen.